Dinámicas grupales para fortalecer el desarrollo integral del niño de Inicial 2 de la Escuela de Educación Básica Benjamin Franklin,Cantón Riobamba - Moreno Moreno, Betty Marisol (2024)
The research project presents a study about group dynamics to strengthen the integral development of the child of Initial 2 of the Benjamin Franklin Basic Education School, Riobamba City. The general objective was to determine the application of group dynamics to improve the child's integral development. The methodology used was a qualitative approach, non-experimental research design. The type of research is bibliographic because the information was selected, organized and interpreted, the same that was obtained from digital journals, repositories, web pages, books and articles, and field because it was developed at the scene of the events. We worked with 100% of the population. The technique used was observation and the observation card as an instrument. Then the procedure for data collection was reached, such as the analysis and interpretation of the results obtained and the respective discussion, where graphs and tables were used to demonstrate the problem. Finally, it ends with the conclusions and recommendations that responded to the objectives set out in the research